Evolution of photovoltaic energy system applied to water pumping for irrigation: PHOTOVOLTAIC PUMPING FOR IRRIGATION - Haupenthal, Soni Willian; Vilas Boas, Marcio Antonio; Cruz Siqueira, Jair Antonio; Kazue Tokura , Luciene (Latin American Journal of Energy Research, 2021)
The increase in the price of fossil fuels and the pollution resulting from their burning have encouraged the use of renewable energy to produce electricity, and their applications have increased in recent years mainly for use in irrigation. Photovoltaic projects have been implemented to analyze the feasibility of pumping water. Within this concept, the article aims to present a literature review, linking practical information with existing scientific knowledge, seeking to expand research on the topic and contribute with information on the use of renewable energy for pumping water for irrigation, emphasizing the rationalization water consumption. With the aim of reducing dependence on fossil fuels, seeking solutions to improve the quality of life in the countryside, generating income for agricultural producers with increased productivity. Thus, the efficiency in the use of photovoltaic pumping systems for irrigation was defined, according to the reference bank.